SEASONAL SEMIDECIDUAL FOREST FRAGMENT SOIL SEED BANK AND IT’S RELATIONSHIP WITH CONSERVATION - Soares,João Juares (2017)
ABSTRACT Soil seed banks are the first source of seeds for regeneration after a forest’s disturbance. The present study aims to verify the regeneration potential of the soil seed bank of a Seasonal Semidecidual Forest remnant. The study was carried out at Canchim Farm, CPPSE - Embrapa (São Paulo State, Brazil). Soil samples were collected from the fragment in both the wet and dry seasons. An average of 307.8 seedlings/m2 was found in the dry season and an average of 144 seedlings/m2 was found in the dry station. Twenty six species of trees with viable seeds were found in the soil, mostly pioneer species; among them, Cecropia glaziovi Snethlage was the most abundant pioneer species. The soil seed bank can be considered of great potential for regeneration due to the presence of pioneers, secondary and later species.